Waters transfer laws and its discrepancies, a brief overview in some neighbouring countries, including discussion on Malaysia-Singapore - Rozlinda Mohamed Fadzil; Haniff Ahamat; Rasyikah Md. Khalid (Penerbit Universiti Kebangsaan Malaysia, 2020)
A brief overview of a few neighbouring countries which have different legal regimes in water laws and conflicts. There were water transfer conflicting rules in some countries as against water as a right. The clash between environmental are human rights, constrains of market perspective are also discussed. The first part discussed about the codification of water laws as a right or privilege and products containing water, such as agricultural produce are subjected to trade disciplines and trade barriers. In the case of bulk transfers of fresh water, private contractual remedies and negotiations between the parties or remedies available in public international law were reviewed, rather than the remedies provided for in trade agreements disputes such as in NAFTA. The latter part discussed about GATS and remedies in public international laws pertaining to water ownership and water transfer laws.